Influence of Operating Temperature on the Vibration Characteristics of the Confluence Planetary Row - Tang Changliang; Liu Qirui; Su Bokang (Jixie chuandong)
As a key component of the integrated transmission device of tracked armored vehicles, the confluence planetary row has the advantages of high transmission efficiency, high load capacity and compact space structure, but its working condition is very complex and variable, and the vibration characteristics under the extreme high and low temperature environment directly affect the service performance of the integrated transmission device. In this study, a comprehensive test rig for the vibration of the confluence planetary row is designed and built, and the dynamic characteristics tests of the confluence planetary row gear system are carried out under normal temperature conditions and temperature rise conditions. The results show that under normal temperature conditions, the rotational speed and load power have a greater influence on the system vibration amplitude; and under temperature rise conditions, when the temperature is constant, the load power has a greater influence on the system vibration amplitude in the low frequency band, and the rotational speed plays a dominant role in the high frequency band. When the speed and load power are certain, the influence of temperature on the low frequency region is more obvious, and the higher the temperature, the more obvious the influence will be. The research results have theoretical and application values for condition monitoring and health maintenance of the confluence planetary row under complex working conditions.